Utilizing Wild Cajanus platycarpus, a Tertiary Genepool Species for Enriching Variability in the Primary Genepool for Pigeonpea Improvement - Sharma, Shivali; Paul, Pronob J.; Sameer Kumar, CV; Nimje, Chetna (Frontiers in Plant Science, 2020)
The use of crop wild relatives in the breeding program has been well recognized to diversify the genetic base along with introgression of useful traits. Cajanus platycarpus (Benth.) Maesen, an annual wild relative belonging to the tertiary genepool of pigeonpea, possesses many useful traits such as early maturity, high protein content, photoperiod insensitivity, and pod borer tolerance for the genetic improvement of cultivated pigeonpea. Using this cross incompatible wild Cajanus species, an advanced backcross population was developed following the embryo rescue technique. In the present study, a pre-breeding population consisting of 136 introgression lines (ILs) along with five popular varieties (used as checks) was evaluated for important agronomic traits during 2016 and 2017 rainy seasons and for grain nutrient content during 2016, 2017, and 2018 rainy seasons. Large genetic variation was observed for agronomic traits such as days to 50% flowering, number of pods per plant, pod weight per plant, grain yield per plant, and grain nutrients [protein content, grain iron (Fe), zinc (Zn), calcium (Ca), and magnesium (Mg)] in the pre-breeding population. Significant genotype × environment interaction was also observed for agronomic traits as well as grain nutrients indicating the sensitivity of these traits to the environments. No significant correlations were observed between grain yield and grain nutrients except grain Zn content which was negatively correlated with grain yield. Overall, 28 promising high-yielding ILs with high grain nutrient content were identified. These ILs, in particular, ICPP # 171012, 171004, 171102, 171087, 171006, and 171050 flowered significantly earlier than the popular mega variety, ICPL 87119 (Asha) and thus hold potential in developing new short-duration cultivars. The comprehensive multi-site assessment of these high-yielding, nutrient-rich accessions would be useful in identifying region-specific promising lines for direct release as cultivars. Moreover, these ILs are expected to replace the popular existing cultivars or for use as new and diverse sources of variations in hybridization programs for pigeonpea improvement.